Response to urban challenges by global cities within developmental states: The case of Tokyo and Seoul - Shahed Khan; Megumi Khan; Sang Kyung An (International Journal of Management and Economics, 2019)
Tokyo and Seoul, the two leading East Asian global cities, operate under "developmental states." They often struggle for control over major urban initiatives against their strong state government agencies as they seek prominence in the global city hierarchy. Through comparative review of approaches to national policy development, this paper traces the similarities of the two countries in approaching national economic development and how that influences their capital city's capacity to manage growth and urbanization pressures. We focus on some major urban development initiatives in Tokyo and Seoul between 1970 and 2010 to test the notion whether global cities get "disembedded" from their state or national context as they integrate into the globalized economy. We contend that national and local societal developments continue to drive the cities' growth patterns, albeit influenced by overall global forces, while the global cities and their nation states evolve ways to compete and collaborate in the pursuit of common interests.
Keywords: O20; R0; 650; global city; developmental state; global projects